Yield and Economics of Other Field Crops in Rain-fed upland cultivation in the Jaffna Peninsula of Dry Zone of Sri Lanka - Vijayathasan, S.; Selvanathan, N. (University of Jaffna, 2015)
The study was done to evaluate six common Other Field Crops (OFC) that belong to three major crop groups, grain legumes, coarse grains and oil crops cultivated as Marginal uplands under fully rain-fed conditions for three consecutive Maha seasons for their agronomic and economic performance at the agricultural Research Station, Thirunelvely. During first raining the land was ploughed and harrowed by four wheel tractor to ensure good weed control suitable for planting. The every variety of seeds was row sowed as rain fed Marginal land during October to November. Rainfall received from October to February (crop growing period) in Maha2006/07 of 751 mm, Maha 07/08 of 916.5 mm and Maha 08/09 of 1246.8 mm were adequate to produce satisfactory yield in all crops. The yield ranges of the crops were 850-1000 kg/ha in blackgram (Vigna mungo) ,350-1050 kg /ha in green gram(Vigna radiata),350-800 kg/ha in cowpea(Vigna unquiculata) ,450-700 kg/ha in finger millet(Eleusine coracana),1500-2000kg/ha in maize (Zea mays )and 1015 kg/ha in groundnut(Arachis hypogaea). Ground nut gave the highest net return (Rs.78500/ha) followed by, black gram (Rs.66666/ha) maize (Rs.62500/ha) and green gram (Rs. 39000/ha), including family labour. However in Maha season cultivation of cowpea and finger millet was not profitable. It can be concluded that green gram black gram, maize and ground nut are suitable crops for marginal rain-fed upland in dry zone of Sri Lanka.
Keywords: Dry Zone; Grain legume; Marginal; Rain-fed; Upland